Measuring customer serving time at TH Seremban toward better and quality delivery / Bibi Hajarah Hasrap (Faculty of Business and Management, 2008)
This research paper objective are to identifies first, the relevant serving period at TH counter, second, to identify the causes of service delay at the counter and the third is to find a way to minimize the serving period for the aim to serve better an quality delivery at TH counter. This study highlight the importance of service quality and how delayed service affect customers, service quality and employee performances. The study intends to provide a comprehensive understanding on the causes of delayed service at the counter. Extensive observation on the serving period had been done at TH counter for the purpose to measure the actual serving time and compared the results of the observation with the SST set by TH. This study is based on simple random sampling where its target population is the users of TH Seremban services. Besides collecting secondary data, primary data also had been collected using questionnaires that have been distributed to 150 respondents. The most important findings of this study is to identify the applicable period of serving customers at TH, second is to identify any causes of services delayed and to find any way to minimize the serving period in order to serve better and quality delivery. The findings of this study will help TH to improve their service quality to the world standard. As we know, TH is leading institution in Malaysia as well as in the world that provides financial planning's for Muslims in Malaysia to perform Haj and Umrah, thus it is necessary for TH to always evaluates their service performance in order to meet the World standard and to be the most successful leading institution in providing financial planning for Muslims all over the world in performing Haj and Umrah.